Coronary plaque quantification and fractional flow reserve by coronary computed tomography angiography identify ischaemia-causing lesions - Gaur, Sara; Ovrehus, Kristian Altern; Dey, Damini; Leipsic, Jonathon; Botker, Hans Erik; Jensen, Jesper Moller; Narula, Jagat; Ahmadi, Amir; Achenbach, Stephan; Ko, Brian S.; Christiansen, Evald Hoj; Kaltoft, Anne Kjer; et al. (European Heart Journal, 2016)
AIMS: Coronary plaque characteristics are associated with ischaemia. Differences in plaque volumes and composition may explain the discordance between coronary stenosis severity and ischaemia. We evaluated the association between coronary stenosis severity, plaque characteristics, coronary computed tomography angiography (CTA)-derived fractional flow reserve (FFRCT), and lesion-specific ischaemia identified by FFR in a substudy of the NXT trial (Analysis of Coronary Blood Flow Using CT Angiography: Next Steps). METHODS AND RESULTS: Coronary CTA stenosis, plaque volumes, FFRCT, and FFR were assessed in 484 vessels from 254 patients. Stenosis >50% was considered obstructive. Plaque volumes (non-calcified plaque [NCP], low-density NCP [LD-NCP], and calcified plaque [CP]) were quantified using semi-automated software. Optimal thresholds of quantitative plaque variables were defined by area under the receiver-operating characteristics curve (AUC) analysis. Ischaemia was defined by FFR or FFRCT ≤0.80. Plaque volumes were inversely related to FFR irrespective of stenosis severity. Relative risk (95% confidence interval) for prediction of ischaemia for stenosis >50%, NCP ≥185 mm(3), LD-NCP ≥30 mm(3), CP ≥9 mm(3), and FFRCT ≤0.80 were 5.0 (3.0-8.3), 3.7 (2.4-5.6), 4.6 (2.9-7.4), 1.4 (1.0-2.0), and 13.6 (8.4-21.9), respectively. Low-density NCP predicted ischaemia independent of other plaque characteristics. Low-density NCP and FFRCT yielded diagnostic improvement over stenosis assessment with AUCs increasing from 0.71 by stenosis >50% to 0.79 and 0.90 when adding LD-NCP ≥30 mm(3) and LD-NCP ≥30 mm(3) + FFRCT ≤0.80, respectively. CONCLUSION: Stenosis severity, plaque characteristics, and FFRCT predict lesion-specific ischaemia. Plaque assessment and FFRCT provide improved discrimination of ischaemia compared with stenosis assessment alone.
EVALuna2:12095